Selective activation of the hypothalamic orexinergic but not melanin-concentrating hormone neurons following pilocarpine-induced seizures in rats - He, Zhenquan; Wang, Xiao; Ma, Kang; Zheng, Leyi; Zhang, Yan; Liu, Chunhong; Sun, Tao; Wang, Peng; Rong, Weifang; Niu, Jianguo (Frontiers in Neuroscience, 2022)
Sleep disorders are common comorbidities in patients with temporal lobe epilepsy (TLE), but the underlying mechanisms remain poorly understood. Since the lateral hypothalamic (LH) and the perifornical orexinergic (ORX) and melanin-concentrating hormone (MCH) neurons are known to play opposing roles in the regulation of sleep and arousal, dysregulation of ORX and MCH neurons might contribute to the disturbance of sleep-wakefulness following epileptic seizures. To test this hypothesis, rats were treated with lithium chloride and pilocarpine to induce status epilepticus (SE). Electroencephalogram (EEG) and electromyograph (EMG) were recorded for analysis of sleep-wake states before and 24 hr after SE. Double-labeling immunohistochemistry of c-Fos and ORX or MCH was performed on brain sections from the epileptic and control rats. In addition, anterograde and retrograde tracers in combination with c-Fos immunohistochemistry were used to analyze the possible activation of the amygdala to ORX neural pathways following seizures. It was found that epileptic rats displayed prolonged wake phase and decreased non-rapid eye movement (NREM) phase compared to the control rats. Prominent neuronal activation was observed in the amygdala and the hypothalamus following seizures. Interestingly, in the LH and the perifornical nucleus, ORX but not MCH neurons were significantly activated (c-Fos+). Neural tracing showed that seizure-activated (c-Fos+) ORX neurons were closely contacted by axon terminals originating from neurons in the medial amygdala. These findings suggest that the spread of epileptic activity from amygdala to the hypothalamus causes selective activation of the wake-promoting ORX neurons but not sleep-promoting MCH neurons, which might contribute to the disturbance of sleep-wakefulness in TLE.